Raptor levels are critical for β-cell adaptation to a high-fat diet in male mice - Manuel Blandino-Rosano; Ruy Andrade Louzada; Joao Pedro Werneck-; Camila Lubaczeuski; Joana Almaça; Markus A. Rüegg; Michael N. Hall; Gil Leibowitz; Ernesto Bernal-Mizrachi (Elsevier, 2023)
Objective: The essential role of raptor/mTORC1 signaling in β-cell survival and insulin processing has been recently demonstrated using raptor knock-out models. Our aim was to evaluate the role of mTORC1 function in adaptation of β-cells to insulin resistant state. Method: Here, we use mice with heterozygous deletion of raptor in β-cells (βraHet) to assess whether reduced mTORC1 function is critical for β-cell function in normal conditions or during β-cell adaptation to high-fat diet (HFD). Results: Deletion of a raptor allele in β-cells showed no differences at the metabolic level, islets morphology, or β-cell function in mice fed regular chow. Surprisingly, deletion of only one allele of raptor increases apoptosis without altering proliferation rate and is sufficient to impair insulin secretion when fed a HFD. This is accompanied by reduced levels of critical β-cell genes like Ins1, MafA, Ucn3, Glut2, Glp1r, and specially PDX1 suggesting an improper β-cell adaptation to HFD. Conclusion: This study identifies that raptor levels play a key role in maintaining PDX1 levels and β-cell function during the adaptation of β-cell to HFD. Finally, we identified that Raptor levels regulate PDX1 levels and β-cell function during β-cell adaptation to HFD by reduction of the mTORC1-mediated negative feedback and activation of the AKT/FOXA2/PDX1 axis. We suggest that Raptor levels are critical to maintaining PDX1 levels and β-cell function in conditions of insulin resistance in male mice.